Total Synthesis of Bryostatin 8 and (–)-Exiguolide: Applications of an Organosilane Strategy - Zhang, Yuebao; Lu, Ji; Li, Hongze; Sun, Xianwei; Gao, Lu; Song, Zhenlei (Synlett, 2019)
In this Account, we give an overview of our recent efforts towards the total synthesis of two marine natural products: bryostatin 8 and (–)-exiguolide. The central theme is to highlight the power of the organosilane strategy, which was characterized with our geminal bis(silanes)-based methodologies for constructing the unique exocyclic enoate-substituted pyran rings.1 Introduction2 Background of Bryostatins and (–)-Exiguolide3 Constructing the B-Ring of Bryostatins4 Total Synthesis of (–)-Exiguolide via an Organosilane Strategy5 Constructing the C-Ring of Bryostatins6 Total Synthesis of Bryostatin 87 Conclusion
Keywords: total synthesis; macrolides; organosilane; Prins cyclization; Brook rearrangement